Pengaruh Budaya Organisasi Dan Gaya Kepemimpinan Terhadap Kinerja Karyawan PT. Asasta Nusantara Group Melalui Kepuasan Kerja Sebagai Variabel Intervening - Tuhu Setya Ning Tyas; Ari Sulistyowati; Bayu Senopitoyo (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research investigates the effects of organizational culture and leadership style on employee performance at PT Asasta Nusantara Group, with job satisfaction as an intervening variable. Using a quantitative approach, the study sampled all 52 employees and analyzed the data with SmartPLS 4.0 software. The results reveal that organizational culture positively influences job satisfaction and employee performance. Leadership style also positively affects job satisfaction and employee performance. However, while job satisfaction positively impacts employee performance, leadership style does not mediate the relationship between job satisfaction and performance. In contrast, organizational culture does mediate this relationship.